Analysis of Contributing Components to Depth Error for Multibeam Echosounding - Wibowo, Wahyu Arif; Wisayantono, Dwi; Windupranata, Wiwin (Indonesian Journal of Geospatial, 2018)
To achieve a high-quality depth data from MBES measurement, the error of depth should be carefully considered, especially in shallow water. To purpose of this research are (1) identifying the error budget of components into depth error and the error contribution components of depth and (2) analyzing the depth error real with an error model. Total depth error comprises of following components, which are range error, beam angle error, pitch error, roll error, sound velocity error, heave error, draught error, and water level error. These errors should be transformed into an error in depth. The equation of depth error contributions will be defined using the method of propagation of errors. Furthermore, the depth error of MBES is evaluated by standards of IHO SP-44. The results is the maximum error is water level error and the minimum error is pitch error. The errors of range, beam angle, roll, and pitch as follow: σr = ± 0.01 m, σθ = ± 0.05º, σRP = ± 0.05º, can determine the depth total error that meets the special order of IHO standard. The results of total depth error model and total depth error real achieve the same level of IHO standard.